2014
DOI: 10.1111/dmcn.12488
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of arginase deficiency revisited: guanidinoacetate as a therapeutic target and biomarker for therapeutic monitoring

Abstract: Hyperargininaemia is a disorder of the last step of the urea cycle. It is an autosomal recessive disease caused by deficiency of liver arginase‐1 and usually presents later in childhood with progressive neurological symptoms including marked spasticity. In contrast with other urea cycle disorders, hyperammonaemia is not usually present but can be a feature. A number of guanidine compounds may accumulate in the blood and cerebrospinal fluid of these patients, which could play an important pathophysiological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 13 publications
(40 reference statements)
0
44
0
1
Order By: Relevance
“…GAA levels exceed reference ranges in patients with ARG1 deficiency. Whether GAA plays a part in the pathophysiology of ARG1 deficiency is an interesting question under the perspective that lowering GAA levels by arginine restriction and ornithine supplementation (Schulze and Battini 2008)aspracticed in GAMT deficiency could be a new therapeutic option in ARG1 deficiency (Amayreh et al 2014). The significantly elevated GAA levels in GAMT deficiency are considered neuropathogenic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GAA levels exceed reference ranges in patients with ARG1 deficiency. Whether GAA plays a part in the pathophysiology of ARG1 deficiency is an interesting question under the perspective that lowering GAA levels by arginine restriction and ornithine supplementation (Schulze and Battini 2008)aspracticed in GAMT deficiency could be a new therapeutic option in ARG1 deficiency (Amayreh et al 2014). The significantly elevated GAA levels in GAMT deficiency are considered neuropathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is a substrate for the enzyme arginine-glycine amidinotransferase (AGAT), which forms guanidinoacetate (GAA) and ornithine from glycine and arginine (Schulze and Battini 2008). GAA enhances oxidative stress in the rat brain (Zugno et al 2008) and these changes have been hypothesized to contribute to the central nervous system (CNS) pathophysiology in guanidinoacetate:methyltransferase (GAMT) deficiency (Amayreh et al 2014;Grioni et al 2014;Kolling and Wyse 2010). It has been suggested that elevated plasma GAA contributes to neuropathology in ARG1 deficiency (Amayreh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Guanidinoacetate can be elevated in patients with urea cycle defects such as arginase deficiency, although creatine concentrations tend to be normal or mildly elevated in this situation. 69,70 While not a CDS indicator, it is worth noting that elevated creatine in plasma has been suggested as a potential biomarker for mitochondrial disorders. 71,72 In general, the use of creatinine as a biomarker for the diagnosis of CDSs (aside from the creatine-to-creatinine ratio for CRTR deficiency) is of limited value.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably related to the chemical stability of unsubstituted internal nitrogen atom and the absence of the methyl group in GAA (Ellington 2001). Elevated GAA levels were also found by Amayreh et al (2014) in the blood and cerebrospinal fluid of patients with arginase deficiency, an autosomal recessive disease caused by deficiency of arginase-1, yet the degree of GAA utilization as an energy donor in this disorder is currently unknown.…”
Section: Introductionmentioning
confidence: 99%